Fodor's 2009 Puerto Vallarta - Onstott, Jane.; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to Puerto Vallarta, with maps and information on accommodations and restaurants, shopping and entertainment, and interesting tourist sites.
Cover title: Puerto Vallarta 2009 :.
Includes index.
Young Adult
Keywords: Guadalajara (Mexico) -- Guidebooks; Puerto Vallarta (Mexico) -- Guidebooks; San Blas (Mexico) -- Guidebooks; Guadalajara (Mexico) -- Guidebooks; Puerto Vallarta (Mexico) -- Guidebooks; San Blas (Mexico) -- Guidebooks